EFFECT OF PRE-TREATMENTS AND DRYING METHODS ON PHYSICO-CHEMICAL QUALITY OF DEHYDRATED PEA (PISUM SATIVUM L.) - MAHESH YADAV; RAJESH GUPTA; ANKIT PANDEY; DHARMENDRA PATIDAR (The Bioscan, 2015)
A study on effect of pre-treatments and drying methods on physico-chemical quality of dehydrated pea was conducted which comprised of twenty treatment combinations, four level of pre-treatments viz., untreated, blanching with NaCl for 3 min (10% and 15%), blanching with KMS for 3 min (0.05% and 0.1% KMS) and four level of drying methods viz., sun drying, solar drying, microwave drying, mechanical drying including one control without any treatment under different drying methods. Among the tested treatments, the pre-treatment of blanching with 15% NaCl for 3 min was found best which exhibited minimum drying time (0.43 h), moisture content (5.97%), loss in weight (73.53%) and maximum recovery (26.27%) whereas among the tested drying methods, the mechanical drying was found best which exhibited maximum protein content (23.62%) with loss in weight (73.53%). Therefore, it can be concluded that treatment combination of blanching with 15% NaCl for 3 min with mechanical drying was found best for most of the physical and chemical characteristics of dehydrated pea.